The effectiveness of an instructional guide on Chinese pre-service EFL teachers' knowledge in teaching phonics - Minjie Chen; Hock Seng Goh; Ruey Shing Soo; Guojie Yin (Universitas Syiah Kuala, 2022)
In China, phonics instruction has been given substantial emphasis ever since the implementation of the 2011 National English Curriculum for Compulsory Education. However, many Chinese students' learning outcome remains unsatisfactory due to EFL teachers' insufficient knowledge to teach phonics and the absence of a phonics instructional guide. To address this gap, this study aims to investigate the effects of a newly developed phonics instructional guide on Chinese pre-service EFL teachers' knowledge base to teach phonics. Adopting an experimental research design, the study was conducted at a teachers' college in Sichuan Province, China. There were 172 pre-service EFL teachers assigned into two equivalent groups, namely the experimental group (N=86) and control group (N=86), who took a test respectively before and after the intervention. The measures of the test included seven dimensions aiming to elicit knowledge of general phonics, phonetic system, phonemic awareness, phonics decoding rules, phonics instructions, reinforcement methods, and sight word instructions. The experimental group participants undertook a 15-hour phonics training course using the newly developed Phonics Instructional Guide (PHOInG). The control group participants were taught using a conventional method involving the use of an English textbook prescribed by the college. Results revealed that the Chinese pre-service EFL teachers in the experimental group improved significantly in their overall knowledge base of English phonics and phonics instruction, except for phonemic awareness and knowledge of the phonetic system. These findings point to the importance of using a needs-based and theoretically informed instructional guide when providing phonics and phonics instruction training to Chinese EFL pre-service teachers.